SHOULD RELIGION HAVE A PUBLIC ROLE? Theologizing from the Filipino Context - Astorga, Christina A (Asian Horizons, 2012)
Should religion have a public role? Should it be engaged in the public arena? Or should religion be kept a private affair? Addressing this question, this article is developed in three parts: first, the meaning of religion; second, the debate on the public role of religion; and third, theologizing from the Filipino context. This question is pursued in the face of the growing secularization in the world which marginalizes religion, and decimates its value as a social reality. Those who argue against the public role of religion privatizes it, or reduces its reach of influence only to its adherents. This article presents the varied positions in the debate on the public role of religion, and validates religion as a force of change and transformation in the Filipino context.